2022
DOI: 10.1519/jsc.0000000000004260
|View full text |Cite
|
Sign up to set email alerts
|

No Changes in Body Composition in NCAA Division I Collegiate Football Players because of COVID-19 Restrictions

Abstract: Czeck, MA, Roelofs, EJ, Evanoff, NG, and Dengel, DR. No Changes in body composition in NCAA Division I Collegiate Football Players due to COVID-19 restrictions. J Strength Cond Res 36(6): 1749-1752, 2022-The purpose of this study was to explore the impact of coronavirus disease 2019 (COVID-19) restrictions on body composition, assessed by dual x-ray absorptiometry (DXA), between the 2020 postseason (pre-COVID-19 restrictions) and the 2021 postseason (post-COVID-19 restrictions) in collegiate football players (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Moreover, recent studies have shown that the body composition was not changed in athletes during the COVID-19 detraining period due to maintaining an adequate training stimulus and having well-available training facilities. 20 , 21 , 44 Our results showed that RTS days and T hours were positively correlated ( r = 0.62 to 0.64) with BM, while RTT days were positively correlated ( r = 0.57) with BF after infection ( Table 4 ). These results suggest that athletes performing a general training routine quickly could mitigate the detraining effect on body composition after infection.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Moreover, recent studies have shown that the body composition was not changed in athletes during the COVID-19 detraining period due to maintaining an adequate training stimulus and having well-available training facilities. 20 , 21 , 44 Our results showed that RTS days and T hours were positively correlated ( r = 0.62 to 0.64) with BM, while RTT days were positively correlated ( r = 0.57) with BF after infection ( Table 4 ). These results suggest that athletes performing a general training routine quickly could mitigate the detraining effect on body composition after infection.…”
Section: Discussionmentioning
confidence: 64%
“… 17 , 18 Furthermore, the effects of RTS during the pandemic on maintaining body composition in athletes remain mixed results. 19 , 20 , 21 Given above, it is necessary to elucidate the influences of ARinf and RTS in athletes who demand high-level neuromuscular function and optimum body composition, such as kayakers. 22 , 23 …”
Section: Introductionmentioning
confidence: 99%
“…It could be assumed that those residents had a more severe complications of the disease, accompanied by a worse nutritional status. Likewise, there are several epidemiological studies in which no changes were reported in body composition or nutritional status in recovered COVID-19 patients, both older and younger ones [ 12 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%